Optimization of the Mixture Design of Low-CO2 High-Strength Concrete Containing Silica Fume - Seung-Jun Kwon; Xiao-Yong Wang (Advances in Civil Engineering)
As abundant CO2 is released by high-strength concrete due to its high binder content, the reduction of CO2 emissions has become increasingly important. This study proposed a general procedure to optimize the mixture design of low-CO2 high-strength concrete containing silica fume. First, the equations for evaluating strength and slump were regressed based on available experimental results. CO2 emissions were calculated based on the concrete mixtures and the unit CO2 emissions of the concrete components. By using the genetic algorithm, the concrete mixtures with the lowest CO2 emissions were determined by considering various constraints. Second, the cost of concrete was calculated based on the concrete mixtures and the unit cost of the concrete components. Similarly, the concrete mixtures with the lowest cost were determined based on the genetic algorithm. We found that, in some cases, the mixtures with the lowest CO2 emissions were different from those with the lowest cost. Third, through adding the constraint equation of cost, Pareto optimal mixtures with relatively lower CO2 emissions and lower cost were determined. In summary, the proposed technique is valuable for designing high-strength concrete considering both CO2 emissions and cost.